Simulation of direct contact membrane distillation regeneration of liquid desiccant solutions used in air-conditioning - Duong, Hung Cong; Tran, Lan Thi Thu (Vietnam Journal of Science and Technology, 2020)
Membrane distillation (MD) has great potential for the treatment of hyper saline waters, including liquid desiccant solutions used in air-conditioning systems. Previous experimental investigations have demonstrated the technical feasibility of MD for regeneration of liquid desiccant solutions. In this study, a direct contact membrane distillation (DCMD) process of the LiCl liquid desiccant solution was simulated using MATLAB software. The simulation was first validated using data obtained from experimental tests. Then, it was used to elucidate the water temperatures, LiCl concentration, and water flux profiles along the membrane leaf inside the DCMD membrane module. Finally, with the help of the simulation, the effects of membrane properties and process operating conditions on the DCMD process performance were systematically examined. The results obtained from this simulation enrich the knowledge and hence facilitate the realization of MD for the liquid desiccant solution regeneration application.